Identification and characterization of a novel Drosophila melanogaster glutathione S-transferase-containing FLYWCH zinc finger protein. - Dai, M.S.; Sun, X.X.; Qin, J.; Smolik, S.M.; Lu, H. (Gene, 2004)
Glutathione SH-transferase (GST) is a 25-kDa protein and a member of a large family that plays a critical role in the cellular homeostasis of all organisms. In this report, we describe a novel GST-containing protein identified and cloned from Drosophila. This 1045 amino acid protein possesses a zinc finger domain with a tandem array of four FLYWCH zinc finger motifs at its N-terminus and a C-terminal domain that shares a 46% homology with GST. The gene maps to chromosome 3 at position 84C6. Further characterization of this protein shows that it localizes to the cytoplasm of fly cells and is expressed through all stages of fly embryonic development. It binds to glutathione-S agarose beads in vitro. These results indicate that this new protein belongs to the GST family, thus named a Drosophila GST-containing FLYWCH zinc finger protein (dGFZF).